Valorization of plastic wastes for production of fuels and value-added chemicals through pyrolysis – A review - Kartik, S.; Balsora, H.K.; Sharma, M.; Saptoro, Agus; Jain, R.K.; Joshi, J.B.; Sharma, A. (ELSEVIER, 2022)
Recycling of waste plastics is a promising solution to deal with the pressure on fuel economy in forthcoming years and to address the concern regarding its accumulation in the environment. Municipal Solid Waste (MSW) is a dominant source of plastic waste. Waste management principles can be applied for resource recovery and energy generation. Pyrolysis, a thermochemical recycling method, holds multiple advantages in relation to product utility, energy input and environmental footprint. The focus of this review is to investigate the potential of pyrolysis to convert waste plastic stream comprising of a mixture of High-Density Polyethylene (HDPE), Low Density Polyethylene (LDPE), Polypropylene (PP) and Polystyrene (PS) into fuel and value-added products (VAP). Concentrated efforts are made to analyse process conditions to maximize production of utilizable fractions (gas and oil) and value-added chemicals through pyrolysis. Behaviour of plastic waste components under different process conditions with reaction mechanisms in both catalytic and non-catalytic pathways are explored and summarized. Discussions on the importance of kinetic, particle and reactor scale to develop a process scheme for pyrolysis process, futuristic research directions are also presented. This paper also critically reviews utility requirements and well-established commercial process to comply with environmental legislations.